Strategi Manajemen Keberlanjutan dalam Era Digital: Tantangan dan Peluang - Nungki Indraty TK (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
In today's digital era, sustainability management has become a key focus for organizations worldwide. Digital transformation not only impacts the way businesses operate but also brings new challenges and opportunities for sustainability. This research aims to explore sustainability management strategies that organizations can implement to address emerging challenges and capitalize on opportunities presented in the digital context. Using a literature review approach, this research examines various relevant previous studies, including the role of information and communication technology (ICT) in sustainability management and the influence of artificial intelligence (AI) on sustainability performance. The results indicate that the integration of ICT and AI into sustainability management strategies can improve operational efficiency and support better decision-making. Furthermore, the importance of digital literacy in raising sustainability awareness is also identified as a key factor. Thus, this research provides valuable insights for practitioners and academics in formulating effective sustainability management strategies in the digital era. It also highlights the importance of collaboration between various stakeholders to achieve broader sustainability goals.